Talking About the â€œMisunderstandingâ€ in the Process of Literary Accepting - Junliu, Xu (Bina Nusantara University, 2008)
The â€œmisunderstandingâ€ in the process of literary accepting refers to the receiver in the reading text process with the creation main body, creation motive, the work implication, as well as between the works artistic value constitutes the situation which â€œthe dialogâ€ in the complex relations produces contradicts. But, in the concrete reading process, the â€œmisunderstandingâ€ may divide in â€œthe error correctionâ€ and â€œinstead harmsâ€ kind of situations. Although â€œthe error correctionâ€ refers to reader's understanding in line with author's creation original meaning which produces contradicts, but the work itself actually has demonstrated readerâ€™s understood connotation, thus causes this kind of the â€œmisunderstandingâ€ seems cuts with actual and persuasiveness. â€œInstead harmsâ€ refers to the reader unconscious determination to carry on the far-fetched cognition and the appraisal to the literary work, including to literary work non-artistic angle of view twisting. â€œThe error correctionâ€ should advocate that â€œinstead harmsâ€ should deny, this does not dispute. But, â€œthe error correctionâ€ and â€œinstead harmsâ€ between has certain fuzzy regions, between them the strict demarcation line, some literary work in such time, possibly has not had â€œthe error correctionâ€ in such receiver, but in another time, possibly has the different understanding in other receivers, to â€œinstead harmsâ€ direction transformation. The â€œmisunderstandingâ€ is the literature accepts the necessity, because just having the â€œmisunderstandingâ€, the different sound, between the literature mutual exchanges and collides, the literature only then had prosperously, the vigorous development aspect.